Case Report: Moderate-to-severe paravalvular leak regurgitation after recurrent prosthetic valve endocarditis in a patient with a double-chambered right ventricle associated with a restricted membranous ventricular septal defect - Sacra, Cosimo; Totaro, Antonio; Triggiani, Giuseppe; Romano, Andrea; Astore, Pasquale; Galluccio, Chiara; Onorato, Eustaquio Maria (Frontiers in Cardiovascular Medicine, 2025)
BackgroundManaging aortic paravalvular leak (PVL) regurgitation following multiple surgical aortic valve replacements (SAVRs) due to recurrent infective endocarditis (IE) presents significant clinical challenges.Case summaryA 46-year-old woman with a history of severe aortic regurgitation and an asymptomatic membranous ventricular septal defect underwent SAVR with a bioprosthetic aortic valve (Perimount 23 mm) in 2005. Concomitantly, a double-chambered right ventricle was diagnosed. Ten years later, due to recurrent IE, another bioprosthetic valve replaced the previous valve (Magna Ease #25). In 2018, she developed sepsis from Bordetella hinzii endocarditis, leading to a third SAVR in 2019, this time with a mechanical aortic valve (On-X® #23). In 2024, two-dimensional transesophageal echocardiography (TEE) revealed moderate-to-severe PVL regurgitation near the right coronary cusp. After a multidisciplinary evaluation, transcatheter PVL closure was planned. Under general anesthesia and TEE/angio-fluoroscopic guidance, the PVL was successfully crossed via the right femoral artery, and a 10 mm × 4 mm Occlutech paravalvular leak device was deployed. Post-procedural imaging confirmed effective PVL closure with a trace-mild residual leak.DiscussionThis case highlights the feasibility of transcatheter PVL closure as a less invasive alternative for patients with multiple prior SAVRs and high surgical risk. Advanced imaging techniques were crucial in procedural success, ensuring precise device placement. A multidisciplinary heart team approach is essential for optimizing outcomes in complex valve pathology. Long-term follow-up is necessary to monitor the durability of the closure and potential complications.